Preparation method and application of magnetron sputtering high-entropy nitriding composite coating
The high-entropy nitriding composite coating prepared by magnetron sputtering technology solves the electrochemical corrosion problems of titanium-based bipolar plates in the proton exchange membrane electrolysis hydrogen production technology, achieves excellent corrosion resistance and conductivity, reduces costs, and is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411956803.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-03-28
AI Technical Summary
In the proton exchange membrane electrolysis hydrogen production technology, the titanium-based bipolar plate is prone to electrochemical corrosion and oxidation problems under local oxygen-rich acidic environment on the anode side, resulting in a decrease in conductivity and a shortened electrolytic cell life.
Magneto-controlled sputtering technology was used to prepare a high-entropy amorphous nitrided composite coating of TiZrNbTaW and TiZrNbTaWN0.75. By injecting nitrogen during the sputtering process, the nitride TiZrNbTaWNx is synthesized by in-situ doping nitrogen elements to form a dense and uniform multi-layer composite coating.
The coating exhibits excellent corrosion resistance and high conductivity in 0.5M H2SO4 plus 5ppm fluorine ion corrosive solution, which reduces the polarization voltage of the electrolytic cell, extends the life, and avoids the high cost of precious metal coatings.
Smart Images

Figure CN119710596A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment, and in particular to a preparation method and application of a magnetron sputtering high-entropy nitriding composite coating. Background Art
[0002] As one of the key technical means to solve the problem of renewable energy consumption, proton exchange membrane water electrolysis hydrogen production technology has the advantages of rapid response, strong fluctuation adaptability, high electrolysis efficiency, high hydrogen production purity, high working current density and compact structure. It is one of the most promising technologies in the field of water electrolysis hydrogen production in recent years. The proton exchange membrane electrolyzer is mainly composed of membrane electrode, gas diffusion layer and bipolar plate. Among them, the bipolar plate is the core component of the proton exchange membrane electrolyzer, which undertakes important functions such as mechanical support, electrical contact, reactant and product transportation and heat transfer.
[0003] At present, pure titanium is the mainstream material for preparing bipolar plate substrates. However, although titanium is a corrosion-resistant material, it still has serious electrochemical corrosion and oxidation problems in the local oxygen-rich acidic environment on the anode side and under high operating voltage conditions. Corrosion may generate oxides, dissolved metal ions or other by-products, and accumulate on the bipolar plate, diffusion layer and membrane electrode surface, thereby affecting its mechanical strength and conductivity, causing the electrolytic cell polarization voltage to increase, efficiency to decrease, and life to shorten.
[0004] In view of this, in order to prevent the bipolar plate substrate from severe corrosion and oxidation, which leads to a decrease in conductivity, additional coatings are needed for protection. Platinum, gold and other precious metal coatings coated on titanium substrates have been commercialized and applied, becoming the mainstream protective coating system currently used by manufacturers. However, the expensive precious metal protective coating system has greatly increased capital investment, making the large-scale promotion of proton exchange membrane water electrolysis technology challenging.
[0005] In recent years, high entropy alloys have broken through the design concept of traditional single main element alloys and have attracted much attention for their excellent corrosion resistance and other properties. The high corrosion resistance of high entropy alloys mainly comes from four core effects: high entropy effect, lattice distortion effect, slow diffusion effect and cocktail effect. The high entropy alloy system is composed of five or more equal or nearly equal metals, covering a variety of element selections, and the performance regulation methods are rich and diverse. In addition to maintaining high corrosion resistance, it is also required to have high conductivity and low interface contact resistance in the application field of proton exchange membrane water electrolysis. Therefore, it is still necessary to select a suitable material system based on the characteristics of this application field, adopt an appropriate preparation process for coating preparation, and carry out targeted performance testing and evaluation.
[0006] Common methods for preparing high entropy alloy coatings include laser cladding, plasma spraying and electrochemical deposition. The melting process of high entropy alloys is relatively complicated, and the preparation technology involving high-temperature melting processes is prone to cause element segregation and shrinkage, which affects the structure and performance and is not conducive to corrosion resistance. The difficulty of electrochemical deposition lies in finding a suitable electrolyte so that multiple ions can be dissolved in the solution at a specific temperature. Summary of the invention
[0007] The embodiments of the present application provide a method for preparing a magnetron sputtering high-entropy nitriding composite coating and its application, with the aim of providing a film layer with low cost, good corrosion resistance and oxidation resistance.
[0008] In order to solve the above technical problems, the technical solution proposed in this application is:
[0009] The present invention provides a method for preparing a magnetron sputtering high entropy nitriding composite coating, comprising the following steps:
[0010] S1: preparing a TiZrNbTaW alloy target, wherein the molar ratio of each element in the alloy target is 1:1:1:1:1;
[0011] S2: metal substrate treatment, the metal substrate treatment comprising: grinding and polishing the metal substrate to a mirror surface and performing ultrasonic cleaning;
[0012] S3: magnetron sputtering deposition process, the magnetron sputtering deposition process comprising:
[0013] S31: sputtering pre-treatment, the sputtering pre-treatment comprising: evacuating the deposition chamber to a predetermined vacuum degree, heating the metal substrate, removing water vapor, adjusting the positional relationship between the metal substrate and the target material, and rotating the target material;
[0014] S32: pre-sputtering, the pre-sputtering comprising: introducing an inert gas as a working gas, maintaining vacuum and pressure in the deposition chamber, shielding a baffle with a cover in front of the metal substrate, and pre-sputtering for a certain period of time at a sputtering power of 120 W to remove surface impurities;
[0015] S33: magnetron sputtering, the magnetron sputtering includes: removing the baffle, controlling the prohibition / input of high-purity nitrogen under certain power conditions, depositing TiZrNbTaW coating and TiZrNbTaWN 0.75 Nitriding coating to form TiZrNbTaWN x Composite coating, where 0≦x≦0.75.
[0016] Furthermore, the sputtering pre-treatment specifically includes: evacuating the deposition chamber to a vacuum of 5×10 -4pa, the metal substrate was baked at 350 °C for 1 hour to remove the water vapor inside the deposition chamber. The temperature was maintained at 350 °C during the deposition process. The deposition surface of the substrate was 80 mm away from the target and rotated at a speed of 10 rpm.
[0017] Furthermore, the pre-sputtering specifically includes: introducing 24 sccm high-purity argon as the working gas, maintaining vacuum to maintain the deposition chamber pressure at a dynamic balance of 0.5 Pa, shielding the front of the substrate with a covered baffle, and pre-sputtering for 30 minutes at a sputtering power of 120 W to remove surface scaling and oxide impurities.
[0018] Further, in the S33, the magnetron sputtering specifically includes: fixing the sputtering power to 170W, removing the baffle and continuing the sputtering for 4 hours, during which, at a certain time interval, high-purity nitrogen gas with a gas flow rate of 5%-15% is turned off or introduced to form a certain thickness of TiZrNbTaW and TiZrNbTaWN 0.75 High entropy amorphous nitride composite coating.
[0019] Furthermore, in the step S33, high-purity nitrogen is completely prohibited from entering, and the TiZrNbTaWN x The composite coating is a TiZrNbTaW high entropy amorphous alloy coating.
[0020] Furthermore, in the step S33, high-purity nitrogen is input throughout the process, and the TiZrNbTaWN x Composite coating is TiZrNbTaWN 0.75 High entropy amorphous nitride ceramic coating.
[0021] Furthermore, the TiZrNbTaWN x The composite coating is composed of TiZrNbTaW and TiZrNbTaWN 0.75 Alternating formation.
[0022] Furthermore, in step S1, high-purity Ti powder, Zr powder, Nb powder, Ta powder and W powder are uniformly mixed in an equimolar ratio by powder metallurgy, and sintered into a target material through vacuum high temperature.
[0023] Further, in S2, the polished metal substrate is ultrasonically cleaned in deionized water, ethanol and acetone, respectively, and then dried in warm air.
[0024] Furthermore, the metal substrate includes pure titanium, titanium alloy, steel, aluminum alloy, copper alloy, and magnesium alloy.
[0025] On the other hand, the present application also seeks to protect a magnetron sputtering high entropy nitriding composite coating, which is a coating prepared on the metal substrate by any of the preparation methods described above.
[0026] On the other hand, the present application also seeks to protect a proton exchange membrane electrolyzer bipolar plate, wherein the bipolar plate is used as the metal substrate, and the coating on the surface of the bipolar plate is prepared by any of the preparation methods described above.
[0027] Compared with the prior art, the preparation method of the present invention has achieved the following beneficial technical effects:
[0028] The coating prepared by the method of the present application has a dense and uniform structure, has excellent corrosion resistance in a corrosive solution of 0.5M H2SO4 plus 5ppm fluoride ions, and has high conductivity, that is, low resistivity. It shows excellent comprehensive performance with a full non-precious metal element composition, overcomes the high cost disadvantage of the current precious metal protective coating in the field of proton exchange membrane water electrolysis, provides a new solution for the field of protective coatings with both corrosion resistance and conductivity, and is suitable for application in large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 The TiZrNbTaW and TiZrNbTaWN prepared by the present invention 0.75 TiZrNbTaWN x SEM morphology of the coating cross section and surface, where (a) is the TiZrNbTaW coating prepared in Example 1, and (b) is the TiZrNbTaWN coating prepared in Example 2 0.75 Coating, (c) is TiZrNbTaWN prepared in Example 3 x Coating, (i) is the cross-sectional morphology, (ii) is the surface morphology.
[0031] Figure 2 The TiZrNbTaW and TiZrNbTaWN prepared by the present invention 0.75 EDS element content values of the coating prepared with other nitrogen concentration parameters, where (a) is nitrogen and (b) is metal element.
[0032] Figure 3 This is the potentiodynamic polarization curve of the prepared coating in a corrosive solution of 0.5 M H2SO4 plus 5 ppm fluoride ions.
[0033] Figure 4This is a third-party test report on the self-corrosion current density of the coating prepared in Example 3 in a corrosive solution of 0.5M H2SO4 plus 5ppm fluoride ions based on the potentiodynamic polarization curve.
[0034] Figure 5 This is a third-party test report on the surface resistivity of the coating prepared in Example 3. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A method for preparing a magnetron sputtering high entropy nitriding composite coating of the present invention comprises the following steps:
[0037] S1: preparing a TiZrNbTaW alloy target, wherein the molar ratio of each element in the alloy target is 1:1:1:1:1;
[0038] S2: metal substrate treatment, the metal substrate treatment comprising: grinding and polishing the metal substrate to a mirror surface and performing ultrasonic cleaning;
[0039] S3: magnetron sputtering deposition process, the magnetron sputtering deposition process comprising:
[0040] S31: sputtering pre-treatment, the sputtering pre-treatment comprising: evacuating the deposition chamber to a predetermined vacuum degree, heating the metal substrate, removing water vapor, adjusting the positional relationship between the metal substrate and the target material, and rotating the target material;
[0041] S32: pre-sputtering, the pre-sputtering comprising: introducing an inert gas as a working gas, maintaining vacuum and pressure in the deposition chamber, shielding a baffle with a cover in front of the metal substrate, and pre-sputtering for a certain period of time at a sputtering power of 120 W to remove surface impurities;
[0042] S33: magnetron sputtering, the magnetron sputtering includes: removing the baffle, controlling the prohibition / input of high-purity nitrogen under certain power conditions, depositing TiZrNbTaW coating and TiZrNbTaWN 0.75 Nitriding coating to form TiZrNbTaWN x Composite coating, where 0≦x≦0.75.
[0043] This application aims at the difficulties in coating selection and preparation in the technical field, adopts magnetron sputtering technology to prepare coating, and synthesizes nitride TiZrNbTaWN by in-situ doping nitrogen element by introducing nitrogen gas during the sputtering process. x By accurately controlling the preparation parameters such as nitrogen content, a dense and uniform multi-layer composite coating is synthesized, which exhibits excellent performance with a completely non-precious metal element composition. It has excellent corrosion resistance in a corrosive solution of 0.5M H2SO4 plus 5ppm fluoride ions. At the same time, it has high conductivity, that is, low resistivity, which overcomes the high cost disadvantage of precious metal protective coatings and is suitable for application in large-scale industrial production.
[0044] In one embodiment of the present application, the sputtering pre-treatment specifically includes: evacuating the deposition chamber to a vacuum of 5×10 -4 pa, the metal substrate was baked at 350 °C for 1 hour to remove the water vapor inside the deposition chamber. The temperature was maintained at 350 °C during the deposition process. The deposition surface of the substrate was 80 mm away from the target and rotated at a speed of 10 rpm.
[0045] In one embodiment of the present application, the pre-sputtering specifically includes: introducing 24 sccm high-purity argon as the working gas, maintaining vacuum so that the pressure in the deposition chamber maintains a dynamic balance of 0.5 Pa of gas pressure, providing a covered baffle in front of the substrate, and pre-sputtering for 30 minutes at a sputtering power of 120 W to remove scale and oxide impurities on the surface.
[0046] In one embodiment of the present application, in S33, the magnetron sputtering specifically includes: fixing the sputtering power to 170W, removing the baffle and continuing sputtering for 4 hours, during which, at a certain time interval, closing or introducing high-purity nitrogen with a gas flow rate of 5%-15%, to form a certain thickness of TiZrNbTaW and TiZrNbTaWN 0.75 High entropy amorphous nitride composite coating.
[0047] In one embodiment of the present application, in S33, high-purity nitrogen is completely prohibited from entering, and the TiZrNbTaWN x The composite coating is a TiZrNbTaW high entropy amorphous alloy coating.
[0048] In one embodiment of the present application, in S33, high-purity nitrogen is input throughout the process, and the TiZrNbTaWN x Composite coating is TiZrNbTaWN 0.75 High entropy amorphous nitride ceramic coating.
[0049] In one embodiment of the present application, the TiZrNbTaWN x The composite coating is composed of TiZrNbTaW and TiZrNbTaWN 0.75 Alternating formation.
[0050] In one embodiment of the present application, in step S1, a powder metallurgy method is used to uniformly mix high-purity Ti powder, Zr powder, Nb powder, Ta powder and W powder in an equimolar ratio, and sinter them into a target material through vacuum high temperature.
[0051] In one embodiment of the present application, in S2, the polished metal substrate is ultrasonically cleaned in deionized water, ethanol and acetone respectively, and then dried in warm air.
[0052] In one embodiment of the present application, the metal substrate includes pure titanium, titanium alloy, steel, aluminum alloy, copper alloy, or magnesium alloy.
[0053] The present application also includes an implementation of a magnetron sputtering high entropy nitriding composite coating, wherein the coating is a coating prepared on the metal substrate by the aforementioned preparation method.
[0054] As an application, the present application also includes a proton exchange membrane electrolyzer bipolar plate, with the bipolar plate as the metal substrate, and the coating on the surface of the bipolar plate is prepared by any of the preparation methods described above.
[0055] like Figure 1-5 As shown, the present application is further introduced below in conjunction with embodiments:
[0056] Example 1: Preparation of a corrosion-resistant, highly conductive TiZrNbTaW high-entropy amorphous alloy coating
[0057] The first step is to prepare an equiatomic ratio TiZrNbTaW target for magnetron sputtering by the following method:
[0058] By powder metallurgy, high-purity (≥99.99%) Ti powder, Zr powder, Nb powder, Ta powder and W powder with equal atomic composition ratio (1:1:1:1:1) are uniformly mixed, and sintered at high temperature in vacuum to preferably form a single circular target with a diameter of 6.3 mm and a thickness of 2 mm for magnetron sputtering deposition of coating.
[0059] The second step is substrate treatment
[0060] The substrate is made of metal, preferably pure titanium, titanium alloy, steel, aluminum alloy, copper alloy, magnesium alloy. Use a grinder and polisher to grind and polish the substrate deposition surface to a mirror-like state without scratches using sandpaper with different meshes of 1200, 800, 400, and 100, polishing cloth, and polishing paste. Ultrasonic cleaning is performed in deionized water, ethanol, and acetone, respectively, and then dried in warm air.
[0061] The third step is magnetron sputtering deposition of TiZrNbTaW high entropy amorphous alloy coating
[0062] Use a mechanical pump and a vacuum pump to evacuate the deposition chamber to 5×10 -4 pa pressure to ensure a pure vacuum environment. Start the substrate heating program and bake at 350℃ for 1 hour to remove water vapor inside the chamber. Maintain 350℃ during the deposition process to maintain good adhesion. The substrate deposition surface is 80mm away from the target and rotates at 10 rpm to ensure uniform thickness of the deposited film. 24sccm of high-purity argon (≥99.99%) is introduced as the working gas, and the mechanical pump and vacuum pump are kept pumping to maintain a dynamic balance of 0.5Pa pressure in the deposition chamber. A covered baffle is used to shield the front of the substrate, and pre-sputtering is performed at a sputtering power of 120W for 30 minutes to remove scaling and oxides. The sputtering power is fixed at 170W, the baffle is removed and sputtering is continued for 4 hours to form a 1.4-micron TiZrNbTaW high-entropy total coating.
[0063] Example 2: Preparation of TiZrNbTaWN 0.75 High Entropy Amorphous Nitride Ceramic Coating
[0064] Step 1: The target material preparation process is the same as that in Example 1.
[0065] Step 2: The substrate treatment process is the same as in Example 1.
[0066] The third step is magnetron sputtering deposition of TiZrNbTaWN 0.75 High Entropy Amorphous Nitride Ceramic Coating
[0067] Use a mechanical pump and a vacuum pump to evacuate the deposition chamber to 5×10 -4 pa pressure to ensure a pure vacuum environment. Start the substrate heating program and bake at 350℃ for 1 hour to remove water vapor inside the chamber. Maintain 350℃ during the deposition process to maintain good adhesion. The substrate deposition surface is 80mm away from the target and rotates at 10 rpm to ensure uniform thickness of the deposited film. High-purity argon is introduced as the working gas, and the mechanical pump and vacuum pump are kept pumping to maintain a dynamic balance of 0.5Pa pressure in the deposition chamber. A covered baffle is provided in front of the substrate, and pre-sputtering is performed at a sputtering power of 120W for 30 minutes to remove scaling and oxides. The sputtering power is fixed at 170W, and the baffle is removed for continuous sputtering for 4 hours. During this period, high-purity nitrogen (≥99.99%) with a gas flow ratio of 5-15% is introduced as a nitrogen-doped reactive sputtering working gas to form 1.35 micron TiZrNbTaWN 0.75 High entropy amorphous nitride ceramic coating.
[0068] Example 3: Preparation of TiZrNbTaWN x High entropy amorphous nitriding composite coating
[0069] Step 1: The target material preparation process is the same as that in Example 1.
[0070] Step 2: The substrate treatment process is the same as in Example 1.
[0071] The third step is magnetron sputtering deposition of TiZrNbTaWN x High entropy amorphous nitriding composite coating
[0072] Use a mechanical pump and a vacuum pump to evacuate the deposition chamber to 5×10 -4 pa pressure to ensure a pure vacuum environment. Start the substrate heating program and bake at 350℃ for 1 hour to remove the water vapor inside the chamber. Maintain 350℃ during the deposition process to maintain good adhesion. The substrate deposition surface is 80mm away from the target and rotates at 10 rpm to ensure uniform deposition film thickness. High-purity argon is introduced as the working gas, and the mechanical pump and vacuum pump are kept pumping to maintain a dynamic balance of 0.5Pa pressure in the deposition chamber. A covered baffle is provided in front of the substrate, and pre-sputtering is performed at a sputtering power of 120W for 30 minutes to remove scaling and oxides. The sputtering power is fixed at 170W, and the baffle is removed for continuous sputtering for 4 hours. Every 30 minutes, high-purity nitrogen (≥99.99%) with a gas flow ratio of 5-15% is turned off or introduced as a nitrogen-doped reactive sputtering working gas to form TiZrNbTaW and TiZrNbTaWN of about 1.28 microns. 0.75 A total of 8 alternating layers of high entropy amorphous nitride composite coating.
[0073] In addition, the composite coating can also be made into 12 layers or 4 layers, and the corresponding nitrogen flow time is 20 minutes or 60 minutes.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a magnetron sputtering high entropy nitriding composite coating, characterized in that: The following steps are involved: S1: preparing a TiZrNbTaW alloy target, wherein the molar ratio of each element in the alloy target is 1:1:1:1:1; S2: metal substrate treatment, the metal substrate treatment comprising: grinding and polishing the metal substrate to a mirror surface and performing ultrasonic cleaning; S3: magnetron sputtering deposition process, the magnetron sputtering deposition process comprising: S31: sputtering pre-treatment, the sputtering pre-treatment comprising: evacuating the deposition chamber to a predetermined vacuum degree, heating the metal substrate, removing water vapor, adjusting the positional relationship between the metal substrate and the target material, and rotating the target material; S32: pre-sputtering, the pre-sputtering comprising: introducing an inert gas as a working gas, maintaining vacuum and pressure in the deposition chamber, shielding a baffle with a cover in front of the metal substrate, and pre-sputtering for a certain period of time at a sputtering power of 120 W to remove surface impurities; S33: magnetron sputtering, the magnetron sputtering includes: removing the baffle, controlling the prohibition / input of high-purity nitrogen under certain power conditions, depositing TiZrNbTaW coating and TiZrNbTaWN 0.75 Nitriding coating to form TiZrNbTaWN x Composite coating, where 0≦x≦0.
75.
2. The preparation method according to claim 1, characterized in that: The sputtering pre-treatment specifically includes: evacuating the deposition chamber to a vacuum of 5×10 -4 pa, the metal substrate was baked at 350 °C for 1 hour to remove the water vapor inside the deposition chamber. The temperature was maintained at 350 °C during the deposition process. The deposition surface of the substrate was 80 mm away from the target and rotated at a speed of 10 rpm.
3. The preparation method according to claim 1, characterized in that: The pre-sputtering specifically includes: introducing 24 sccm high-purity argon as the working gas, maintaining vacuum to maintain a dynamic balance of 0.5 Pa pressure in the deposition chamber, shielding the front of the substrate with a covered baffle, and pre-sputtering for 30 minutes at a sputtering power of 120 W to remove surface scaling and oxide impurities.
4. The preparation method according to claim 1, characterized in that: In S33, the magnetron sputtering specifically includes: fixing the sputtering power to 170W, removing the baffle and continuing the sputtering for 4 hours, during which, at a certain time interval, closing or introducing a high-purity nitrogen gas with a gas flow rate of 5%-15%, to form a certain thickness of TiZrNbTaW and TiZrNbTaWN 0.75 High entropy amorphous nitride composite coating.
5. The preparation method according to claim 1, characterized in that: In the S33, high-purity nitrogen is completely prohibited, and the TiZrNbTaWN x The composite coating is a TiZrNbTaW high entropy amorphous alloy coating.
6. The preparation method according to claim 1, characterized in that: In the step S33, high-purity nitrogen is input throughout the process, and the TiZrNbTaWN x Composite coating is TiZrNbTaWN 0.75 High entropy amorphous nitride ceramic coating.
7. The preparation method according to claim 1, characterized in that: The TiZrNbTaWN x The composite coating is composed of TiZrNbTaW and TiZrNbTaWN 0.75 Alternating formation.
8. The preparation method according to claim 1, characterized in that: In step S1, high-purity Ti powder, Zr powder, Nb powder, Ta powder and W powder are uniformly mixed in an equimolar ratio by powder metallurgy, and sintered into a target material at a high temperature in vacuum.
9. The preparation method according to claim 1, characterized in that: In S2, the polished metal substrate is ultrasonically cleaned in deionized water, ethanol, and acetone, respectively, and then dried in warm air.
10. The preparation method according to claim 1, characterized in that: The metal substrate includes pure titanium, titanium alloy, steel, aluminum alloy, copper alloy and magnesium alloy.
11. A magnetron sputtering high entropy nitriding composite coating, characterized in that: The coating is a coating on the metal substrate prepared by the preparation method according to any one of claims 1 to 10.
12. A bipolar plate for a proton exchange membrane electrolyzer, characterized in that: The bipolar plate is used as the metal substrate, and the coating on the surface of the bipolar plate is prepared by the preparation method according to any one of claims 1 to 10.
Citation Information
Cited By
Titanium-based high-entropy amorphous / tungsten multilayer film with anti-irradiation and low-hydrogen retention potential and preparation method and application of titanium-based high-entropy amorphous / tungsten multilayer film
CN120291038A